Carbon dot-based nanomaterials: a promising future nano-platform for targeting tumor-associated macrophages - Miao, Yingying; Wang, Shuang; Zhang, Butian; Liu, Lin (Frontiers in Immunology, 2023)
The tumor microenvironment (TME) is the internal environment that tumors depend on for survival and development. Tumor-associated macrophages (TAMs), as an important part of the tumor microenvironment, which plays a crucial role in the occurrence, development, invasion and metastasis of various malignant tumors and has immunosuppressant ability. With the development of immunotherapy, eradicating cancer cells by activating the innate immune system has yielded encouraging results, however only a minority of patients show a lasting response. Therefore, in vivo imaging of dynamic TAMs is crucial in patient-tailored immunotherapy to identify patients who will benefit from immunotherapy, monitor efficacy after treatment, and identify alternative strategies for non-responders. Meanwhile, developing nanomedicines based on TAMs-related antitumor mechanisms to effectively inhibit tumor growth is expected to become a promising research field. Carbon dots (CDs), as an emerging member of the carbon material family, exhibit unexpected superiority in fluorescence imaging/sensing, such as near infrared imaging, photostability, biocompatibility and low toxicity. Their characteristics naturally integrate therapy and diagnosis, and when CDs are combined with targeted chemical/genetic/photodynamic/photothermal therapeutic moieties, they are good candidates for targeting TAMs. We concentrate our discussion on the current learn of TAMs and describe recent examples of macrophage modulation based on carbon dot-associated nanoparticles, emphasizing the advantages of their multifunctional platform and their potential for TAMs theranostics.